(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The European Union (EU) common policy in the field of intellectual property (IP) attracts more and more attention of scientists and practitioners for a number of reasons. It is dynamically developing sector and important factor of economic development in the context of digital transformation. Therefore, this article analyses the institutional and legal structure of the EU IP protection system. Two vectors of modern European policy in the field of IP rights protection are highlighted: internal and external. Their target direction and functional features are outlined. Key subjects of implementation of the EU’s unified policy in the field of IP have been identified: the EU institutions (European Parliament, Council of the EU and European Commission), European Patent Organization, the EU Intellectual Property Office. Their functions and mechanisms of interaction have been established, in particular through the EU Intellectual Property Network. The trends in the development of the system, peculiarities of protection of various categories of IP objects in the EU in the context of modern technological achievements, digitalization and the COVID-19 pandemic have been revealed. The EU IP objects can be classified into three groups: industrial property (inventions, utility models, industrial designs, trademarks, indication of the origin; objects of copyright and related rights (literary works, works of art, computer programs, databases, performances, phonograms and videograms, programs of broadcasting organizations) and other objects of IP rights (plant varieties, animals, topography of integrated microcircuits, etc. Today, the EU IP policy is aimed at improving the ways of protection IP rights, strengthening their use (primarily in business), promoting licensing and common use, ensuring better counteraction to IP rights violations and promoting fair play at the global level. It is one of the most effective in the world, harmoniously combined with the processes of development of the single market, increasing the dynamism and competitiveness of the EU economy, the formation of an information society with a high degree of innovative and investment attractiveness.